31 Physical Activity, Muscle Strength and Quantity: Preliminary Findings From the Mass_Lifecourse Cohort. (16th March 2021) - Bowden-Brown, K J; Murray, J C; Hurst, C; Granic, A; Sayer, A A; Dodds, R M
Abstract: Introduction: We established the MASS_Lifecourse study to investigate changes in skeletal muscle between ages 45–85. Reduced physical activity (PA) is a key factor linked to the development of sarcopenia. Our aim was the describe the amount and patterns of PA and sedentary behaviour (SB), and relationships with muscle strength and quantity, among MASS_Lifecourse participants. Method: Participants wore a triaxial accelerometer on their dominant wrist for seven days. Recordings were analysed to calculate time in moderate-vigorous PA (MVPA) with time not in MVPA classified as SB based on wrist position. Muscle strength was measured with a Jamar grip dynamometer and the 5 chair-stand test. Muscle quantity was assessed using appendicular lean muscle mass from dual-energy X-ray absorptiometry. Physical performance was assessed by gait speed. Results: 68 participants (31 male) aged 47–84 (mean 65) participated in the present study. Median daily MVPA was 19.1 (IQR 7.1, 36.6) minutes and was lower with age. The mean sedentary time per day was 767.1 minutes per day and increased with age. The pattern of MVPA across the day changed with age: the oldest group (75–84 years) achieved a lower morning activity peak followed by an earlier decline whilst the younger groups were more consistently active throughout the day. Participants were more active than population reference data from the Active Lives Survey. Time spent in MVPA was positively associated with muscle strength and physical performance, whereas SB was negatively associated. Muscle quantity was not associated with PA or SB. Conclusions: Participants in the MASS_Lifecourse study are more active than the general population but still show age-related declines in physical activity and strength. Future work in the cohort aims to elucidate mechanisms underlying the age-related loss of muscle strength and quantity.